THE ROLE OF THE COMMUNITY IN THE RELEASE OF UTILIZATION OF BANKS FOR BUSINESS OF ORGANIC BRANCH CULTURE - ELLYUNIZAR ELLYUNIZAR (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2019)
Sumber Jaya peasant women group, Kampung Melayu sub-district, Bengkulu city is a group of women farmers who really need activities to supplement their income. In general, members of the Sumber Jaya peasant women group are residents of low economic backgrounds and have no jobs. Utilization of the yard can produce food, raw materials, industry, or energy sources, and to manage the environment as an effort to utilize biological resources. The activities carried out were cultivation of organic chili and processing of organic chili into shredded chili and candied chili. The stages of the activity are as follows: counseling for organic chili cultivation. The goal to be achieved in this activity is to increase the production of chili cultivation.